Rapid drug detection in whole blood droplets using a desorption electrospray ionization static profiling approach - a proof-of-concept - Fresnais, Margaux; Haefeli, Walter E.; Burhenne, Jürgen; Longuespée, Rémi (Rapid communications in mass spectrometry, 2020)
Rationale The introduction of desorption electrospray ionization (DESI) - and ambient desorption/ionization (ADI) ion sources in general - in the 2000s has opened new possibilities for mass spectrometric (MS) analyses of biological sample surfaces. DESI allows for a rapid screening of solid samples because no sample preparation is needed and the analysis is performed at atmospheric pressure. In the present study, we used DESI as an ion source for the rapid detection of a small molecule in blood droplets deposited on glass slides. Methods Blood was spiked with different concentrations of a model drug, mebendazole. One microliter blood droplets of each preparation were deposited on the surface of a glass slide and analyzed by DESI, either in imaging or profiling mode. Results The results suggested that DESI imaging mode was not appropriate for the detection of mebendazole in blood droplets as an initial solvation time was necessary before the obtention of signal. A profiling approach consisting of analyzing a single position of the blood droplet was used for further analysis and allowed mebendazole to be detected in the fg range and to monitor the volume of sample analyzed. Conclusions The study suggests that profiling mode at a single position is adequate for DESI analyses in whole blood droplets. This proof-of-concept study illustrates the potential of DESI profiling as a possible alternative to liquid chromatography/MS analyses of whole blood, when analyses are needed within a restricted time. Rapid detection methods in blood at atmospheric pressure may find interesting applications in the fields of toxicology and pharmacology.